(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Life skills can be best understood as the abilities for positive and adaptive behaviour that enable individuals to deal effectively with day-to-day needs and challenges. Major life skills include problem solving, decision-making, creative and critical thinking, effective communication, interpersonal skills, empathy, self-awareness, and coping with stress and emotions. These life-skills have further been clustered as thinking skills, social skills, and emotional skills. Adolescence is the period of human growth and development that occurs after childhood and before adulthood, from ages 10 to 19. It represents one of the critical transitions in the life-span and is marked by a tremendous pace of physical and psychological human development. Life-skills are a vast group of psycho-social and interpersonal skills that are needed for every individual to lead a healthy and productive life. These are the skills that help promote mental wellbeing and competence in young people. Adolescence is considered a period of stress and storm in which teenagers go through different physical, emotional, social, and cognitive changes. In this period, teaching life skills education is very important for adolescents because they help them to effectively communicate, think critically and creatively, and make rational decisions in their lives. Life skills education helps empower the youth to act responsibly in society. These life skills are important because they will help teenagers cope with problems they face in their everyday lives. Thus, the present paper intends to explore the challenges and issues of life skills education among adolescents.